God's profound and mysterious providence : as revealed in the genealogy of Jesus Christ from the time of David to the exile in Babylon - Park, Abraham; Wone, Yong Kug. (Singapore : Periplus Editions, 2011)
"The fourth book in the History of Redemption series, God's Profound and Mysterious Providence begins with accounts of King David and Solomon, then continues into the era of divided kingdoms: the northern kingdom of Israel and the southern kingdom of Judah. This book illustrates the reigns and lives of the kings from the perspective of God's administration for redemptive history"--Amazon.com.
God's administration of redemption -- The eternal covenant and providence -- God's providence and everlasting lovingkindness -- The general history and characteristics of the second period in the genealogy -- The basis for the calculation of the regnal chronology in the second period of the genealogy -- The first generation: David -- The second generation: Solomon -- The third generation: Rehoboam -- The fourth generation: Abijah or Abijam -- The fifth generation: Asa -- The sixth generation: Jehoshaphat -- The seventh generation: Jehoram or Joram -- The eighth generation: Uzziah or Azariah -- The ninth generation: Jotham -- The tenth generation: Ahaz -- The eleventh generation: Hezekiah -- The twelfth generation: Manasseh -- The thirteenth generation: Amon -- The fourteenth generation: Josiah -- The generations omitted from the first period in the genealogy of Jesus Christ -- The generations omitted from the second period in the genealogy of Jesus Christ -- The history of the kings of Israel, the Northern Kingdom -- Conclusion: the transmission of faith and the lamp of eternal covenant.
Chronologies inserted before half title.
Series from book cover.
Includes commentary by Dr. Yong-Kuk Wone.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Genealogy; Economy of God; Jews -- History -- 953-586 B.C.; Redemption